RELASI AGAMA SEBAGAI SISTEM KEPERCAYAAN DALAM DIMENSI FILSAFAT DAN ILMU PENGETAHUAN - ZA, Tabrani (UIN Ar-Raniry, 2018)
There are three things that become a tool for humans to search for truth, namely philosophy, science, and religion. Although the purpose of these three aspects is to find the truth, all three cannot be categorized as the same thing (synonym). In general, philosophy is considered something that is very free because he thinks without limits. While religion prioritizes revelation/inspiration from substances that are considered God. Everything that comes from God, from a religious perspective is a truth that cannot be denied. While knowledge is a set of methods to find the truth. Between philosophy and science, both do not have a central figure as religion centralizes God. That is, every problem faced by humans, then they will use three kinds of tools to reach a solution. Some religious experts make philosophy and science as a tool to sharpen understanding of religion so that the truth about religion is stronger. While philosophers see religion with deep thought so that a philosopher gets the most essential truths. As for science, it is actually a very simple tool, because it can be used by everyone in the capacities and abilities of each human being. Understanding of these three aspects is quite urgent for everyone because everyone definitely needs an understanding of the problems faced in daily life.